Pandects of Antiochus in the Church Slavonic Prologue (Based on the Readings of the First Half-Year) - Čistiakova, Marina (Slavistica Vilnensis, 2021)
The article examines the readings from the Pandects of Antiochus as a source for compiling the didactic section of the Church Slavonic Prologue. The research material consists of circa 100 copies of all the known translations and versions of the Prologue for the autumn-winter half-year. In total, 44 readings have been identified as deriving from the Pandects, and in six cases the same sermon is given in two versions. The largest number of readings (21) is present in the extended edition of the Prologue compiled in the 60s of the 12th century. In this group of texts borrowed from the Pandects, the source text has been thoroughly edited. The shortened edition of the Prologue and the subsequent editions of the Prologue compiled on the basis of the oldest versions partially derive from the readings in the extended edition of the Prologue. The Moscow and the Kyrill-Belozersk editions of the Versed prologue were supplemented by individual new readings from the Pandects. The sermons were more actively transferred to the Prologue versions created and/or prevalent in the Grand Duchy of Lithuania, namely, the Kiev-Sophia, the Museum, the Kiev editions and special varieties of the Prologue based on the extended edition.